From Order to Chaos: Essays : Critical, Chaotic and Otherwise - P.Kadanoff Leo (World Scientific, 1993)
This book is a compilation of the review papers, expositions, and some of the technical works of Leo Kadanoff, who is a theoretical physicist. The idea is to put together a group of not-too-technical writing in which he discusses some issues in condensed matter physics, hydrodynamics, applied mathematics and national policy. The first section contains review papers on hydrodynamics, condensed matter physics and field theory. Next, is a selection of papers on scaling and universality, particularly applied to phase changes. A change of pace is provided by a series of papers on the critical analysis of simulation models of urban economic and social development. The book concludes with a series of recent papers on turbulence and chaos. Each major section is introduced in a section designed to tie the work together and to provide perspective on the subject matter